The core curriculum in the Baguio City High School a description and an evaluation of its program - Balinsat, Isabel M. 1936- (s.n.], 1966)
This study described and evaluated the administrative, supervisory and instructional aspects of the Unified Studies Program of the Baguio City High School. It further investigated the extent by which the administrative aspects of the Baguio City High School core program provides for effective learning and the effectiveness of the instruction under the core program, and the place of the core in the 2-2 plan.